Assessing the role of selenium in Minamata disease through reanalysis of historical samples - Mineshi Sakamoto; Masumi Marumoto; Koichi Haraguchi; Takashi Toyama; Yoshiro Saito; Steven J. Balogh; Chiharu Tohyama; Masaaki Nakamura (Environment International)
Minamata disease, a severe neurological disorder identified in Japan in 1956, results from methylmercury (MeHg) intoxication in humans due to environmental contamination. Before MeHg was recognized as the cause, selenium (Se) was suspected of being the potential cause owing to elevated Se levels in patients’ organs. Subsequent animal studies indicated that Se mitigates MeHg toxicity; however, its role in Minamata disease remains unexplored. We analyzed Hg and Se in historical samples of the industrial wastes (n = 4) on the factory site, sediments (n = 9), and fish/shellfish (n = 16) in Minamata Bay, and organs of patients with Minamata disease (n = 12). All samples showed elevated levels of both Hg and Se, providing the first evidence that Se was also discharged into Minamata Bay, entering the food chain and accumulating at high levels in patient organs. The Hg/Se molar ratio in contaminated shellfish (median > 3.0) indicated exceptionally high MeHg exposure, far exceeding the ordinary level (< 1.0). Patients exhibited significantly increased Se levels in the liver and kidney but lower amounts in the brain. Notably, median Hg/Se molar ratios exceeding 4.0 were observed, particularly in the cerebrum and cerebellum in acute cases, closely mirroring the molar ratios found in seafood. The elevated Hg/Se molar ratio in the brain helps explain the severe neurological damage in patients’ central nervous systems, despite higher Hg levels in the liver and kidney compared to the brain. These findings provide important insight into the mechanism of MeHg intoxication and highlight the risks associated with MeHg-contaminated seafood, aiding efforts to protect consumers.